APPRASAL OF THE FACTORS THAT HINDERS EFFECTIVE IMPLEMENTATION OF UNIVERSAL BASIC EDUCATIOM POLICY IN PUBLIC JUNIOR SECONDARY SCHOOLS IN ADAMAWA STATE - Muhammad Satatu Mera (Akademika : Jurnal Teknologi Pendidikan, 2023)
The aim of the research is to identify the factors that hindered the effective implementation of policies in the in junior schools. Therefore, to identify these factors, the paper comes up with four research questions and four research objectives as a guided to the study. Descriptive research design was adopted for the study. Population of the study consisted of 254 junior secondary schools, 4500 teachers and 254 principals in Adamawa state. Sample of the study was drawn using deliberate and stratified random sampling techniques, while proportionate sampling technique was used to determine the sample size required from each school. Data for the study was obtained using questionnaire. Pilot test was conducted using Cronbach Alpha and a reliability index of 0.79 was realized. Data collected was analyzed using frequency counts, percentage, mean and standard deviation while independent T-test was used to test the hypothesis generated. Findings from the study indicated that: insufficient funding, poor planning and inadequate professionally qualified teachers are some of the challenges that mars successful implementation of UBE programme in Adamawa state. It was discovered that the allocation to education in the state is below the 26% recommended by UNESCO and as a result of Poor welfare package (Mean=3.96, SD=0.96), Lack of training & retraining opportunities (Mean=2.98, SD=0.96). The study recommended among others that efforts should be made by the government to counter the factors which has become impediments to successful implementation of UBE programme such as provision of adequate funding, qualified professional teachers and instructional materials.